KUCING PELIHARAAN DALAM KARYA SENI GRAFIS TEKNIK (RELIEF PRINT) - Waris Waris; Irwan Irwan (Universitas Negeri Padang, 2020)
The creation of this final work aims to visualize pet cats related to behavior, character and behavior in the form of graphic art of relief print techniques (high print). The work displays various pet cat behaviors that are often seen. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. The author successfully created 10 works with the title: move children, sharpen nails, pounce on prey, fight, love, waiting for food, playing, friendship, misunderstanding, cohesiveness.Keywords: Pet Cat, Behavior, Relief Print